The Effect of Chitosan Concentration on Growth Dendrobium sonia’s Orchid - Raisah Bani; Parawita Dewanti (Berkala Ilmiah Pertanian, 2022)
Dendrobium orchid is an ornamental plant that has high economic value. The beauty of orchids is considered unique because it has the shape and characteristics of each so much in demand by the public. Based on market analysis the community's interest was dominated by Dendrobium orchid types . The percentage of Desndrobium orchid enthusiasts reached 34% and is the highest percentage compared to other orchid types . The availability of orchid seedlings in Indonesia is still being disrupted. In vitro techniques become breeding techniques that are often used in orchid propagation. Acclimatization is one of the important things in the in vitro technique . Differences in environmental conditions at the acclimatization stage can cause plantlets to over-transpire and interfere with nutrient absorption. Chitosan as a natural organic material is a simple derivative of chitin that can function as a biofertilizer and bioimmuner.Each unit of experiment was repeated 5 times. The parameters observed were leaf width (cm), leaf length (cm), root length (cm), and number of roots. The data obtained were analyzed using the analysis of varians. The results are shown in the study have demonstrated the effect of administration of chitosan on plant orchid Dendrobium sonia at the acclimatization stage.Treatment with a concentration of 3 ppm has a significant effect in increasing plant growth parameters.